The division of labor within firms - Assar Lindbeck; Dennis J. Snower (Institute for International Economic Studies, 1997)
The paper examines the determinants of the division of labor within firms. It provides an explanation of the pervasive change in work organization away from the traditional functional departments and towards multi-tasking and job rotation. Whereas the existing literature on the division of labor within firms emphasizes the returns from specialization and the need for coordination of the work of different workers, the present analysis focuses on the returns from multi-tasking, which is shown to arise from informational and technological complementarities among tasks as well as from the exploitation of the versatility of human capital.
urn:nbn:se:su:diva-40992
Keywords: J23; J24; L23; M12; O33; 330; division of labor; specialization; multi-tasking; organization of work; technological change; information flows